GIS based analytical hierarchical process for ecotourism site suitability assessment / Ainon Nisa Othman ... [et al.] - Othman, Ainon Nisa; Idris, Muhammad Ajmal A’imullah; Hashim, Nurhanisah; Abdul Rasam, Abdul Rauf; Abd Hamid, Akhbaarudin (UiTM Press, 2025)
Ecotourism grounded in environmental conservation and cultural sensitivity and emerges as a powerful tool for promoting tourism while preserving natural and cultural heritage. Lipis district located in Pahang have faces challenges such as illegal logging, thus pushing the needs and necessitating strategic planning for ecotourism sites. The study aims to derive a site suitability map for ecotourism in Lipis district using Geographic Information System (GIS) and Analytic Hierarchy Process (AHP). The objectives are to identifying key criteria influencing site suitability, developing an ecotourism model using GIS (AHP), and analysing the suitability of existing ecotourism areas. The criteria used were land use, slope, elevation, roads and proximity to infrastructure, are validated through expert opinions and past studies. The AHP calculation were done and the scoring of the criteria based on expert’s opinion. Results from the weightage shows the highest values are Land Use, Slope, Elevation, Roads and Infrastructure Proximity. The study concludes by developed a Site Suitability for Ecotourism Model (SSEM) and assessing existing ecotourism sites against the model. Results indicate that the SSEM successfully categorise areas into classes of suitability with Natural Breaks and Equal Interval classification. Overall, the district has a coverage of 9% Very High Suitability, 30% High Suitability, 33% Moderate Suitability, 22% Low Suitability, and 6% Not Suitable. Finally, the existing ecotourism sites in Lipis district align with the model's suitability classes, which mostly located around Very High Suitability and High Suitability rating area with a total value of 39% suitable area thus validating the effectiveness of the approach in site suitability assessment for ecotourism.